Perilaku Cyberbullying pada Pemain Mobile Legends - Dimas Faturrahman Kusumo Nugroho; Moh. Amin Tohari (International Forum of Researchers and Lecturers, 2024)
This study was conducted with the aim of examining cyerbullying behavior that occurs in the Mobile Legends game in the Mobile Legends player community. This study uses theories from Think Before Text, Kowalski (2008), and the Transtheorical Model (1970) using descriptive qualitative research methods, and the method of finding informants using purposive sampling and snowball sampling techniques. The factors that influence the occurrence of cyberbullying are divided into several factors, but the factors that have the most influence on the occurrence of cyberbullying actions include family factors, the environment, and one's nature. As a result of cyberbullying, it will cause behavioral changes in a person, these behavioral changes are preceded by precontemplation, contemplation, preparation, action and maintenance. The factors that influence a person to experience changes in behavior due to cyberbullying are caused by a lack of parental attention in supervising their children's socialization, a poor friendship environment, and unstable emotions, causing changes in the behavior of victims to become cyberbullying perpetrators. Therefore, it is necessary to have supervision from parents in supervising the socialization of their children, the need for self-resistance so as not to fall into negative things in socializing, the need for healthy and sporitf competition in channeling the talent of playing MLBB games, and the need for strict sanctions against perpetrators.